Adult tonsillectomy: Risk factors for postoperative complications - Peça, Rita (2024)
Objective: This study aimed to evaluate surgical indications and risk factors associated with postoperative complications in tonsillectomy in adults. Study design: Retrospective observational study of 539 patients who underwent surgery at a tertiary center between 2016 and 2021. Material and methods: Demographic and clinical data were collected, and the outcomes were defined: post-tonsillectomy hemorrhage; surgical hemostasis in the operating room; emergency department visits for supportive care. Results: The overall incidence of post-tonsillectomy hemorrhage (PTH) was 16.6% and 13.5% of the patients visited the emergency department for pain control. PTH showed statistically significant associations with both surgeon experience (p=0.008) and patient age (p=0.047). Surgical indication was identified as an independent predictor of pain control (p=0.007). Conclusion: These factors, namely surgical indication, patient’s age and surgeon inexperience, play an important role in preventing post-tonsillectomy complications.